Empowerment and Socio-economic Impact of Livelihood Trainings: A Case of a Private Educational Institution in Southern Luzon, Philippines - Lunar, Bernardo C.; Gesmundo, Joseph Christian P.; Alvero, John Cliford M.; Rono, Kyle Aris Dayvid D.; Allic, Clarisa M. (INTI International University, 2023)
This study explored the perceived impact of the livelihood training program on employment and entrepreneurship among participants of San Pablo Colleges' DREAMS Program. This study aimed to understand the extent to which the program has contributed to creating employment and entrepreneurial opportunities for individuals within the community. Through a mixed-methods approach, including surveys and qualitative interviews, data was collected from a diverse group of participants. The findings revealed a mixed response regarding the program's impact on employment and entrepreneurship. Out of the 30 respondents, 10 reported that the livelihood training program helped them create employment and entrepreneurial opportunities, while 20 respondents did not experience significant impact in these areas. The program's overall mean score of 3.03 on a scale of 1 to 5 suggests a moderate impact on participants' employment and entrepreneurial activities. Several factors contributed to the varied outcomes. Individual context played a crucial role, with participants' pre-existing skills, interests, and market conditions influencing their ability to translate the training into viable ventures. For those who experienced positive outcomes, the program facilitated the establishment of income-generating businesses, such as selling various products and providing services like manicure, pedicure, and hair cutting. Implementing the recommended strategies can maximize the program's positive impact and foster sustainable livelihoods among participants, contributing to community empowerment and economic growth.